Anthropometric Characteristics and Body Composition Differences between Rugby Players According to their Specific Playing Position - Pavle Malovic; Dragan Bacovic (Journal of Anthropology of Sport and Physical Education)
This study aimed to determine the differences in anthropometric characteristics and body composition among rugby players of the national team of Montenegro and Bulgaria, according to positions they play. A sample of 30 examinees is divided into four sub-samples and according to positions they are classified as forwards and backs. Anthropometric characteristics and body composition were evaluated by a battery of 11 variables: body height, body weight, six skinfolds, body mass index, body fat, and muscle mass. It was found that forwards were statistically significant taller and heavier than backs in the national team of Montenegro. Also, that forwards of the national team of Bulgaria statistically significant differed than backs in all skinfold variables and body fat percentage, but backs statistically significant differed than forwards in muscle mass. Comparing players of two national teams regarding to positions they play was found that backs of the national team of Montenegro statistically differed than backs of the national team of Bulgaria in biceps, subscapular, and lower leg skinfolds and body fat, but Bulgarians statistically differed than Montenegrins in muscle mass. Comparing forwards, it was found that Bulgarians statistically differed in abdominal, lower leg, and thigh skinfolds. The nominative data of this study may help coaches to detect weak links in rugby specific athletic performance and set a plan and program to improve them.